2020
DOI: 10.1038/s41598-020-79177-2
|View full text |Cite
|
Sign up to set email alerts
|

The androgen receptor expression and its activity have different relationships with prognosis in hepatocellular carcinoma

Abstract: The role of the Androgen Receptor (AR) expression and its activity in the prognosis of hepatocellular carcinoma (HCC) remains inconclusive. The aim of this study is to analyze the role of the AR expression and its activity as prognostic biomarkers in HCC. Three-hundred and thirty-seven patients from The Cancer Genome Atlas (TCGA) (107 females; 59.42 years [SD = 13.0]) were included. To infer AR activity, the expression-profile of previously validated androgen responsive genes (ARGs) was included. AR activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In the nontransplant setting, studies have suggested that sex hormone receptors in the liver mediate most sex disparities in HCC 5,[23][24][25][26] although some other studies have suggested that sex hormones themselves can mediate it 6,27 In the former case, it is reasonably assumed that the difference in overall recurrence rate after LT, if it exists, is attributable to the difference in graft recurrence rate. We specifically analyzed the graft recurrence rate to assess this possibility with higher sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the nontransplant setting, studies have suggested that sex hormone receptors in the liver mediate most sex disparities in HCC 5,[23][24][25][26] although some other studies have suggested that sex hormones themselves can mediate it 6,27 In the former case, it is reasonably assumed that the difference in overall recurrence rate after LT, if it exists, is attributable to the difference in graft recurrence rate. We specifically analyzed the graft recurrence rate to assess this possibility with higher sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not evaluate protein-level AR localization compared to our multigene classi er. However previous studies show that AR RNA-based signatures expression correlate with AR protein expression [55,56].…”
Section: Discussionmentioning
confidence: 98%
“…AKT1 is an important regulator of the tumorigenic processes, migration, Evidence-Based Complementary and Alternative Medicine spreading, therapeutic sensitivity, resistance, survival, and proliferation of LC cells, and is a promising theragnostic target [64][65][66][67]. AR expression and activity influence angiogenesis, stemness, invasion, angiogenesis, epithelialmesenchymal transition (EMT), migration, and oncogenesis of LC cells, and it is a prognostic determinant and responsive marker for anticancer therapies [68][69][70][71][72][73]. EGFR is responsible for the modulation of proliferation, metastasis, migration, self-renewal potential, EMT, angiogenesis, anchorage-independent growth, invasion, and drug sensitivity of LC cells and tumors, and its expression and activity are implicated in the initiation, recurrence, progression, metastasis, and aggressiveness of LC in patients [74][75][76][77][78][79][80][81][82][83].…”
Section: Discussionmentioning
confidence: 99%